Volume 6: Ocean Space Utilization; Ocean Renewable Energy 2016
DOI: 10.1115/omae2016-55008
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Typhoon Loads Effect on the Structural Response of Offshore Meteorological Mast and Wind Turbine

Abstract: Recently, Taiwan started to evaluate the potential of wind energy production on its West coast. The concern was raised about employing existing solutions validated by experience for mild environment regions to Taiwan which is frequently subject to Typhoon. This study investigated the strength under typhoon condition of two offshore wind farm units: a meteorological mast supported by a monopile and a 3.6 MW wind turbine supported by a 4-leg jacket. Especially, two critical load cases were analyzed. First, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Chi et al studied the typhoon impacts on the foundation design of offshore wind turbines [31]. In terms of extreme load effect studies, Lin and Li et al invested the extreme load effects on the structural response of an offshore wind turbine jacket foundation under typhoon conditions [32][33][34]. Huang et al analysed the damage probability of mono-pile OWT under action of typhoon [35].…”
Section: Introductionmentioning
confidence: 99%
“…Chi et al studied the typhoon impacts on the foundation design of offshore wind turbines [31]. In terms of extreme load effect studies, Lin and Li et al invested the extreme load effects on the structural response of an offshore wind turbine jacket foundation under typhoon conditions [32][33][34]. Huang et al analysed the damage probability of mono-pile OWT under action of typhoon [35].…”
Section: Introductionmentioning
confidence: 99%
“…One of the more obvious challenges faced by Taiwan"s wind farms are the extreme loads exerted on the wind turbine and support structures during typhoons [3,4], which strike the island, on average, four times every year [5]. Additionally, the authors previously showed that fatigue damage due to Taiwan"s prevailing North Easterly trade winds can be just as significant a design problem [6].…”
Section: Introductionmentioning
confidence: 99%